Longitudinal effect of curcumin-photodynamic antimicrobial chemotherapy in adolescents during fixed orthodontic treatment: a single-blind randomized clinical trial study - Paschoal, Marco Aurélio Benini; Moura, Cintia Maria Zanin de [UNESP]; Jeremias, Fabiano [UNESP]; Souza, Juliana Feltrin de; Bagnato, Vanderlei Salvador; Giusti, Juçaira Stella Martins; Santos-Pinto, Lourdes Aparecida Martins dos [UNESP] (Springer Nature, 2014)
White spot lesions are one of the concerns during the fixed orthodontic treatment. Thus, the aim of the present study was to evaluate the antimicrobial/anti-inflammatory effect of curcumin-photodynamic antimicrobial chemotherapy (c-PACT) and chlorhexidine varnish on the plaque accumulation and gingival bleeding in adolescents under fixed orthodontic treatment. A randomized clinical trial was performed with an initial number of 45 patients being distributed into three groups: group I—chlorhexidine varnish 2 %, group II—placebo varnish, and group III—c-PACT (curcumin at 1.5 mg.mL−1) exposed to blue Light-emitting diode (LED) light at 450 nm (power density = 165 mW.cm−2, fluency = 96 J.cm−2, total dose = 150.7 J). The treatments were performed for four consecutive times with an interval of 1 week each. After the interventions, two calibrated examiners (Kappa value = 0.75) analyzed the dental plaque accumulation by plaque index (PI) and gingivitis condition by gingival bleeding index (GBI) with 1 and 3 months of follow-up after the treatments comprised a final sample of 35 patients. No significant difference was found to PI between the groups during baseline and 1-month period. Group III (1.52 ± 0.51) presented significance difference from group I (0.91 ± 0.75) and group II (1.03 ± 0.51) at 3 months of follow-up. In this same period, there was more plaque accumulation with significant statistical difference (P ≤ 0.05) in comparison to the other periods to all studied groups. There was a GBI reduction statistically significant to groups I and III at 1-month follow-up in comparison to other periods. No effect was verified to dental plaque accumulation after the photodynamic application mediated with curcumin activated with a blue LED light.
Keywords: Photochemotherapy; Curcumin; Orthodontic appliances